Narrative methods for organizational and communication research - Boje, David M. (SAGE series in management research., 2001)
An essential guide for academics and researchers needing to look at alternative discourse analysis strategies. As a research tool, narrative methods have become increasingly useful in organization studies, where much research involves the interpretation of 'stories' in some form.